1972
DOI: 10.1139/v72-109
|View full text |Cite
|
Sign up to set email alerts
|

Urea–Boron Trihalide Adducts. I. The Boron Trifluoride Adduct of Tetramethylurea

Abstract: Evidence is presented that oxygen is the donor atom in the 1:1 adduct of tetramethylurea and boron trifluoride (TMU•BF3). Hydrogen fluoride, a common impurity in boron trifluoride, leads to the formation of [Formula: see text] as well as TMU•BF3. Exchange reactions among TMU, [Formula: see text]and TMU•BF3 are investigated briefly. The results of the present investigation are compared with the results of a previous study which indicated that nitrogen is the donor atom in BF3 adducts of some partially alkylated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

1972
1972
1986
1986

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 18 publications
1
9
0
Order By: Relevance
“…The TMSeU-BF3 system is very similar. These systems differ from the TMU-BF3 system (1,3) in that the donor-acceptor bond lifetime is much shorter. Exchange of adduct with excess T M T U is rapid on the proton nmr time scale and even at -90 OC no free-TMTU peak could be detected a t 6 3.01 when BF3 was present.…”
Section: Resultsmentioning
confidence: 86%
See 2 more Smart Citations
“…The TMSeU-BF3 system is very similar. These systems differ from the TMU-BF3 system (1,3) in that the donor-acceptor bond lifetime is much shorter. Exchange of adduct with excess T M T U is rapid on the proton nmr time scale and even at -90 OC no free-TMTU peak could be detected a t 6 3.01 when BF3 was present.…”
Section: Resultsmentioning
confidence: 86%
“…Our investigations of the 1 : 1 boron trifluoride adducts of tetramethylurea (TMU) and dialkylureas demonstrated that oxygen was the donor site (1,2). We also found that under appropriate conditions redistribution to give ionic adducts (TMU)2BFZf.BX4-takes place (3).…”
Section: Introductionmentioning
confidence: 80%
See 1 more Smart Citation
“…This confirms that oxygen is the donor site. We now report 'H nmr studies of restricted rotation in the heavier boron trihalide adducts of TMU and in the oxygen-replaced analogue of TMU, 1, l-bis-(dirnethylamino)ethyle~le (2). The adducts of 2 show some additional interesting features.…”
Section: Introductionmentioning
confidence: 93%
“…Results and Discussion Although proton spectra of tetramethylurea (TMU, 1) or its BF3 adduct show no evidence of restricted rotation about the central C-N bonds down to -100 O C (2), restricted rotation has been detected in the TMU.SbC15 adduct (3) and in dialkylurea-BF3 adducts (4). This confirms that oxygen is the donor site.…”
Section: Introductionmentioning
confidence: 96%